2013
DOI: 10.1021/jp406339z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of CO and NO on Composition-Selected Cerium Oxide Cluster Cations

Abstract: The collisional reactions of composition-selected cerium oxide cluster cations, CenOm(+) (n = 2-6; m ≤ 2n), with CO and NO have been investigated under single collision conditions using a tandem mass spectrometer. At near-thermal energy, oxidation of CO and NO is observed only for the stoichiometric clusters, CenO2n(+) (n = 3-5), and the cross sections for the NO oxidation are found to be larger than those for the CO oxidation. In addition, the collision-energy dependence of the reaction cross sections reveals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 39 publications
2
52
2
1
Order By: Relevance
“…The major difference between the two studies was the experimental conditions. The CID study was performed under single-collision conditions (∼10 −4 Torr, 34 namely, 10 12 −10 13 molecules cm −3 ), while in the present study, cluster ions collided with NO and He gases much more frequently in the reaction gas cell, which was a multiple-collision environment (10 17 −10 18 molecules cm −3 ). When the cluster ion formed a complex with a reactant molecule, the clusterreactant complex gained energy equivalent to the collision energy and binding energy.…”
Section: Comparison With Collision-induced Dissociationmentioning
confidence: 87%
See 4 more Smart Citations
“…The major difference between the two studies was the experimental conditions. The CID study was performed under single-collision conditions (∼10 −4 Torr, 34 namely, 10 12 −10 13 molecules cm −3 ), while in the present study, cluster ions collided with NO and He gases much more frequently in the reaction gas cell, which was a multiple-collision environment (10 17 −10 18 molecules cm −3 ). When the cluster ion formed a complex with a reactant molecule, the clusterreactant complex gained energy equivalent to the collision energy and binding energy.…”
Section: Comparison With Collision-induced Dissociationmentioning
confidence: 87%
“…Density functional theory (DFT) calculations suggested that there were two intermediates in the reaction pathway of NO oxidation. 34 One of these intermediates could be described as an NO moiety bound to Ce n O 2n + , while the other was an NO 2 bound to Ce n O 2n−1 + . The two intermediates will hereafter be denoted as Ce n O 2n + NO and Ce n O 2n−1 + NO 2 .…”
Section: Reactivity With Nomentioning
confidence: 99%
See 3 more Smart Citations